Pengaruh Konsentrasi Ekstrak Etanol Daun Salam (Syzygium Polyanthum) Terhadap Hambatan Pertumbuhan Bakteri Enterococcus Faecalis Dominan di Saluran Akar In Vitro - Saputri, Tiara Eka; , drg. Mahmud Kholifa, MDSc; , drg. SE Yuletnawati, MDSc (2015)
Enterococcus faecalis is a Gram-positive anaerobic bacteria which usually found on periapical lesion. It is known as phatogenic bacteria often cause failure on root canal treatment. Herbs usage as an antibacterial agent has been widely applied by people, on of them is bay leaf ( syzygium polyanthum), a herbs contain chemical compound that has antibacterial ability such as tannin, flavonoid and aetheric oil. This study was conducted to examine the effect of bay leaf's (Syzygium Polyanthum) ethanol extract concentration against Enterococcus faecalis growth dominant root canal in vitro. This study was carried by laboratory experiment with posttest only control group design study. The method was disk diffusion method with 7 treatment group, concentration of ethanol extract 2.5%, 5%, 10%, 20%, 40%, sterile aquades as negative control and amoxicillin as positive control. Each group were replicated 3 times. The diameter of appeared inhibitory zone were measured using vernier caliper of 0.02 mm precision. Data analysis was carried on one way ANOVA test (p<0.05), followed by LSD post-hoc test. The result showed that ethanol extract of bay leaf (syzygium polyanthum) on 2.5%, 5%, 10%, 20%, and 40% concentration were effective to impede enterococcus faecalis growth, root canal dominant in vitro.